Autonomous Apartment Exploration, Modelling and Segmentation for Service Robotics. Issue 15 (2016) - Manfredi, Guido; Devin, Sandra; Devy, Michel; Sidobre, Daniel
Abstract: This work proposes a full pipeline for a robot to explore, model and segment an apartment from a 2-D map. Viewpoints are found offline and then visited by the robot to create a 3-D model of the environment. This model is segmented in order to find the various rooms and how they are linked (windows, doors, walls) yielding a topological map. Moreover areas of interest are also segmented, in this case furniture's planar surfaces. The method is validated on a realistic three rooms apartment. Results show that, despite occlusion, autonomous exploration and modeling covers 95% of the apartment. For the segmentation part, 1 link out of 14 is wrongly classified while all the existing areas of interest are found.